Analisis Implementasi UU 33/2014 dan PP 42/2024 terhadap Pengawasan Produk Halal Oleh BPJPH - Muyassaroh Yusroni; Mulfi Aulia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The supervision of BPJPH over halal labeling on food and beverages is still not optimal, especially due to a lack of education for business actors and the public. Many MSMEs have not included halal/non-halal labels in accordance with Law No. 33 of 2014, even though Indonesia has great potential in the halal industry. Halal certification is mandated by law and the latest government regulations, but the challenges of supervision and certification costs remain an obstacle. This study aims to enhance consumer trust and the effectiveness of regulations using qualitative methods through interviews and literature reviews. The research results indicate that supervision is carried out by business actors internally and by BPJPH externally, supported by LPH and MUI. Cases like marshmallow and Warung Ayam Goreng Widuran emphasize the importance of supervised and transparent distribution. Import-export supervision is still limited but is conducted through inter-agency cooperation. BPJPH implements risk-based supervision and gradual sanctions, as well as establishing synergy with various parties. Overall, the supervision process is in accordance with applicable laws and regulations, covering education, certification, label revocation, cooperation both domestically and internationally, and the implementation of SJPH. Products that do not meet the requirements are advised to label themselves as